Gradient of Parvalbumin- and Somatostatin-Expressing Interneurons Across Cingulate Cortex Is Differentially Linked to Aggression and Sociability in BALB/cJ Mice - van Heukelum, Sabrina; Mogavero, Floriana; van de Wal, Melissa A.E.; Geers, Femke E.; França, Arthur S.C.; Buitelaar, Jan K.; Beckmann, Christian F.; Glennon, Jeffrey C.; Havenith, Martha N. (Frontiers in Psychiatry, 2019)
Successfully navigating social interactions requires the precise and balanced integration of emotional and cognitive cues. When such flexible information integration fails, maladaptive behavioral patterns arise, including excessive aggression, empathy deficits and social withdrawal, as seen in disorders such as conduct disorder and autism spectrum disorder. One of the main hubs for the context-dependent regulation of behavior is cingulate cortex, specifically anterior cingulate cortex (ACC) and midcingulate cortex (MCC). While volumetric abnormalities of ACC and MCC have been demonstrated in patients, little is known about the exact structural changes responsible for the dysregulation of behaviors such as aggression and social withdrawal. Here, we demonstrate that the distribution of parvalbumin (PV) and somatostatin (SOM) interneurons across ACC and MCC differentially predicts aggression and social withdrawal in BALB/cJ mice. BALB/cJ mice were phenotyped for their social behavior (3-chamber task) and aggression (resident-intruder task) compared to control (BALB/cByJ) mice. In line with previous studies, BALB/cJ mice behaved more aggressively than controls. The 3-chamber task revealed two sub-groups of sociable versus non-sociable BALB/cJ mice. Sociable BALB-cJ mice were as aggressive as the non-sociable group – in fact, they committed more acts of socially acceptable aggression (threats and harmless bites). PV and SOM immunostaining revealed that a lack of specificity in the distribution of SOM and PV interneurons across cingulate cortex predicted social withdrawal: Both control mice and sociable BALB/cJ mice showed a differential distribution of PV and SOM interneurons across the sub-areas of cingulate cortex, while for non-sociable BALB/cJ mice, the distributions were near-flat. In contrast, both sociable and non-sociable BALB/cJ mice had a decreased concentration of PV interneurons in MCC compared to controls, which was therefore predictive of aggressive behavior. Together, these results suggest that the dynamic balance of excitatory and inhibitory activity across ACC and MCC shapes both social and aggressive behavior.